Teachers’ post-pandemic outlook on the role of Technological and Pedagogical Content Knowledge in coping with burnout under adverse conditions: How a job demand transformed into a job resource - Rastegar, Negar; Rahimi, Mehrak (Frontiers in Psychology, 2023)
The sudden change of instructional mode from face-to-face to online teaching during the COVID-19 pandemic forced teachers to develop their ICT skills and knowledge to cope with newly imposed job pressures. The imbalance between job demands and resources in this context led to teachers’ severe burnout. This retrospective study utilized a mixed methods approach to examine teachers’ coping mechanisms, Technological and Pedagogical Content Knowledge (TPACK), and job burnout amid the COVID-19 pandemic. Data were gathered from 307 teachers on their experience of emergency remote teaching (ERT) at the time they returned to school in the Spring of 2022. Structural Equation Modeling was used to investigate the mediating role of TPACK in the relationship between coping strategies and burnout. The results revealed direct effects in the pathways of avoidant, active positive, and evasive coping to burnout highlighting the role of avoidant strategies in harming teachers’ well-being and problem-focused strategies in promoting teachers’ mental health. Also, indirect effects of active positive coping to burnout through TPACK, as a constructive approach to fighting back the crisis, were verified. Further, the direct effect of TPACK on burnout as a hindrance was significant showing that higher levels of TPACK guaranteed lower job burnout and emotional drain. Analyzing interviews with 31 teachers revealed that TPACK functioned as a stressor at the outset of the pandemic and a resource for overcoming the strain and resolving the challenges in the midst of the crisis till schools reopened. The findings underscore the significant role of teachers’ updated knowledge base in reducing their job pressure and taking proper decisions to cope well with unforeseen circumstances. The study has practical implications for policymakers, teacher educators, and school administrators to pay immediate attention to collective wisdom, organizational support, and technological infrastructures for improving teachers’ well-being and professional success.